Effect of thermal challenge on the expression of genes involved in ovarian steroidogenesis in Tasmanian Atlantic salmon (Salmo salar) - Anderson, K; Pankhurst, Ned; King, Harry; Elizur, A (Aquaculture, 2017)
Thermal challenge typically results in lowered plasma 17β-estradiol and 17,20β-dihydroxy-4-pregnen-3-one, and is associated with poor reproductive performance in commercially important female Atlantic salmon. The aim of the present study was to gauge the thermal sensitivity of genes crucial to ovarian steroidogenesis, and determine how they fit into this endocrine response in reproductive fish of different ages. Exposure to higher-than-normal temperature (22 vs 14 °C) did not significantly impact the expression of forkhead transcription factor or follicle stimulating hormone receptor (fshr) during peak vitellogenesis, although, fshr was lower in thermally challenged maiden fish in the lead up to final oocyte maturation. For the first time, we have demonstrated the temperature-dependent down-regulation of ovarian steroidogenic acute regulatory protein and 3β-hydroxysteroid dehydrogenase in the month preceding ovulation, and now have a better understanding of the mechanism underlying the inability of thermally exposed fish to recover after temperature reduction prior to final oocyte maturation.